2023
DOI: 10.3390/ijerph20021177
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Family Crisis Coping Strategies on Family Quality of Life in the Assessment of Patients with Idiopathic Scoliosis

Abstract: The aim of the study was to assess the impact of the strategies of coping with the family crisis in children and adolescents with idiopathic scoliosis on the level of their family’s quality of life (FQOL). The study group consisted of 100 adolescents (girls 83%, boys 17% of the entire main group) with an average age of 14 (13.83 ± 1.92). The control group consisted of the same number of people as the study group (girls 78%, boys 22% of the entire control group) with an average age of 14 (14.09 ± 2.16). The FQO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Patients will be motivated to recover when receiving support from their families. Research results stated that higher family support will increase self-esteem and selfcontrol, as such increase is expected to help patient's coping ability to face stressors during the illness (Cyran-Grzebyk et al, 2023). Accordingly, Abdi et al (2020) said that a person's independence needs chance, support, and boost from others and society around him/her.…”
Section: Correlation Between Family Support and Self-carementioning
confidence: 99%
“…Patients will be motivated to recover when receiving support from their families. Research results stated that higher family support will increase self-esteem and selfcontrol, as such increase is expected to help patient's coping ability to face stressors during the illness (Cyran-Grzebyk et al, 2023). Accordingly, Abdi et al (2020) said that a person's independence needs chance, support, and boost from others and society around him/her.…”
Section: Correlation Between Family Support and Self-carementioning
confidence: 99%
“…Several studies have shown a significant correlation between the coping mechanisms of family caregivers and the quality of life of T2DM patients (Cyran-Grzebyk et al, 2023;Dewi et al, 2020;Freeman-Hildreth et al, 2019). Well-applied coping strategies align with the family's desires in caring for T2DM patients, thereby enhancing the quality of life through comprehensive family support.…”
Section: Family Coping Strategies and Quality Of Lifementioning
confidence: 99%